AB0272 Bsmi and Foki VDR Gene Polymorphisms Influence Disease Activity in Established Rheumatoid Arthritis Patients. (10th June 2014) - Bernardes, M.; Machado, J.C.; Gonçalves, D.; Abelha-Aleixo, J.; Fonseca, R.; Madureira, P.; Vieira, R.; Bernardo, A.; Martins, M.J.; Costa, L.; Simões-Ventura, F.
Abstract : Background: Vitamin D has been shown to have significant immunomodulatory effects. Its actions are mediated by the ubiquitous vitamin D receptor (VDR). In one study, BsmI VDR gene polymorphism was associated with an early onset of rheumatoid arthritis (RA). Additionally, TT genotype of the FokI VDR gene polymorphism was established as a genetic susceptibility marker for RA in French and Tunisian populations. Objectives: To determine the degree of association of BsmI and FokI VDR gene polymorphisms with disease activity in patients with established RA. Methods: Clinical features and peripheral blood samples were collected from a monitoring visit. The Portuguese version of HAQ and the disease activity scores (DAS28 (4v; ESR), DAS28 (3v; ESR), DAS 28 (4v; CRP), DAS28 (3v; CRP)) were obtained. We measured the following acute phase reactants: ESR and CRP. Genomic DNA was extracted from blood and genotyped for the BsmI (A/G) (rs1544410) and FokI (T/C) (rs 2228570) SNPs by PCR-RFLPs analysis. A multivariate analysis model was used for statistical analysis (IBM SPSS Statistics 21). Results: We evaluated 208 RA patients, 166 (80%) women, 65 (31%) premenopausal women, age 54±12 years, disease duration 14±10 years, mean DAS28 (4v) of 4.25±1.33 and a mean HAQ of 1.254±0.709. In our sample, 107 (51%) were under biologics, 87 (42%) under anti-TNFalpha agents and 42 (20%) under vitamin D supplements. Genotype frequencies were determined for the two distinct VDR polymorphisms: BsmI (GG 37%, 44% AG, AA 19%) and FoKI (CC 42%, TC 46%, TT 12%). GG genotype of the BsmI VDR gene polymorphism was associated with higher DAS28 (4v; ESR), DAS28 (3v; ESR), DAS 28 (4v; CRP) and DAS28 (3v; CRP) scores (p<0.001). Additionally, TT genotype of the FokI VDR gene polymorphism was associated with higher DAS28 (4v; ESR), DAS28 (3v; ESR), DAS 28 (4v; CRP) and DAS28 (3v; CRP) scores (p<0.001). In the subgroup of patients without vitamin D supplements, the previously observed associations remained significant (p<0.001). All these associations were found after adjusting for age, disease duration, current HAQ, time under DMARDs therapy, current average daily dose of prednisone and years of corticosteroid use. Conclusions: In our RA population, the BsmI GG and the FokI TT genotypes of the VDR gene were related with disease severity. In the future, VDR gene polymorphisms could be useful in establishing RA prognosis. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3913